Pathways in Paralympic sport: An in-depth analysis of athletes` developmental trajectories and training histories - Dehghansai, N.; Pinder, R. A.; Baker, J. (Adapted Physical Activity Quarterly, 2021)
This three-part investigation conducted a comprehensive analysis of 213 Australian and Canadian athletes` developmental trajectories, training histories, and experiences in organized sports from 18 Paralympic sports (PS). While athletes with early-onset impairments (i.e., congenital, preadolescent) reached milestones and commenced various types of training at a significantly younger age than athletes with later-onset impairments (i.e., early adulthood, adulthood), the latter groups progressed through their careers and incorporated various trainings at a faster pace (i.e., fewer years). Preferences to certain training conditions varied between groups. Eighty-two percent of the athletes with acquired impairments had experience in able-bodied sports before the onset of their impairment, with 70% noting involvement in sports similar to their current PS. The participation rates (38%) and sport similarity (53%) were lower in PS. The amalgamation of findings from this series of studies highlights the complexity associated with PS athletes` development and demonstrates the importance of taking an individualized approach.